2008
DOI: 10.1080/02652030701584058
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conditions for determination of zinc bacitracin, polymyxin B, oxytetracycline and sulfacetamide in animal feed by micellar electrokinetic capillary chromatography

Abstract: A separation technique for zinc bacitracin, polymyxin B, oxytetracycline and sulfacetamide in animal feedstuffs by micellar electrokinetic capillary chromatography (MEKC) was developed. The running buffer was 20 mmol l(-1) borate, 20 mmol l(-1) phosphate, pH 8.4, containing 20 mmol l(-1) sodium dodecylsulphate and 10% (v/v) methanol. MEKC was performed at 25 degrees C; the applied voltage was 25 kV with a running pressure of 10 mbar. Simultaneous UV detection for all analytes was at 215 nm. The method was vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Varying the physical nature of the micelle (size, charge, geometry) by using different surfactants can yield dramatic changes in selectivity, similar to those obtained by changing the stationary phase in liquid chromatography. The influence of SDS on the migration time was described in our previously published papers [18][19][20][21][22]. The results demonstrated that the SDS concentration dramatically affected the migration time of all investigated compounds due to the changes in viscosity.…”
Section: Surfactant Concentrationmentioning
confidence: 81%
See 2 more Smart Citations
“…Varying the physical nature of the micelle (size, charge, geometry) by using different surfactants can yield dramatic changes in selectivity, similar to those obtained by changing the stationary phase in liquid chromatography. The influence of SDS on the migration time was described in our previously published papers [18][19][20][21][22]. The results demonstrated that the SDS concentration dramatically affected the migration time of all investigated compounds due to the changes in viscosity.…”
Section: Surfactant Concentrationmentioning
confidence: 81%
“…Numerous types of surfactants can be used in MEKC, but SDS is one of the most commonly used [5,6,10,11,[18][19][20][21][22]. In MEKC, selectivity can easily be manipulated.…”
Section: Surfactant Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several analytical techniques used to quantify TCs in feeds: TLC (15), HPLC (4,11,16,17,20), HPCE (11,22), LC/MS, LC-MS/MS (6,8,10), and microbiological assays (15). Nowadays, liquidchromatography coupled with mass spectrometry and tandem mass spectrometry seem to be the techniques of choice for analysis of these groups of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of techniques for sulfonamide detection in feedingstuffs described in recent papers most commonly use chromatographic methods. These methods comprise thin-layer chromatography (TLC) (5), enzyme immunoassay (EIA) (20,27), high performance liquid chromatography (HPLC) with ultraviolet (UV) detection (8,10,13,17,25,26,28), HPLC-UV in premix (28,29), HPLC with diode array detector (DAD) (1,11), HPLC-DAD in premix (2), HPLC with fluorescence detector (FLD) (13,2), HPLC connected to mass spectrometry (MS) (3,14,15,18,19,23), and micellar electrokinetic capillary chromatography (MEKC) with UV detection (12). The study of the literature allowed us to select and successfully optimise the chromatographic method with UV detection as a procedure, which can be easily implemented by any laboratory.…”
Section: Introductionmentioning
confidence: 99%